2020
DOI: 10.1111/imr.12934
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap to a plasma cell: Epigenetic and transcriptional cues that guide B cell differentiation

Abstract: B cell differentiation is a multistep process that ultimately leads to the formation of plasma cells or antibody-secreting cells (ASCs), a specialized cell type that functions as an antibody factory. Once initiated, B cell differentiation encompasses multiple transitory cell types that allow for amplification of responding cells and diversification of the antibody repertoire as well as cell fate endpoints such as antigen-experienced memory and short-and long-lived ASC. Aided by the adoption of genomic profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 119 publications
(271 reference statements)
0
8
0
Order By: Relevance
“…Although there are differences in the cell types that emerge and timing of TI and TD B cell responses, few transcriptional differences in SLPC or LLPC have been identified, suggesting that the processes that lead to ASC formation are likely similar 7,97,98 . Indeed, SLPCs contribute to early protective antibodies to influenza, 99 and more recent work demonstrated that extrafollicular responses correlated with early neutralizing antibodies in critically ill COVID‐19 patients 100 .…”
Section: B Cell Differentiation Is a Coordinated Multistep Processmentioning
confidence: 99%
“…Although there are differences in the cell types that emerge and timing of TI and TD B cell responses, few transcriptional differences in SLPC or LLPC have been identified, suggesting that the processes that lead to ASC formation are likely similar 7,97,98 . Indeed, SLPCs contribute to early protective antibodies to influenza, 99 and more recent work demonstrated that extrafollicular responses correlated with early neutralizing antibodies in critically ill COVID‐19 patients 100 .…”
Section: B Cell Differentiation Is a Coordinated Multistep Processmentioning
confidence: 99%
“…Plasma cell differentiation requires profound transcriptional and epigenetic reprogramming and is linked to cell division ( 7 ). On the one hand, transcriptional reprogramming is accomplished through the interplay of opposing transcriptional networks: PAX5, BCL6, BACH2 and low levels of IRF4 govern B cell and GC B cell fates whereas high levels of IRF4, BLIMP1 and XBP1 dictate the plasma cell program.…”
Section: Introductionmentioning
confidence: 99%
“…Through repression of each other’s expression, the latter gain functional dominance over the former during plasma cell differentiation ( 8 , 9 ). On the other hand, epigenetic reprogramming comprises DNA methylation/and demethylation, histone modification and chromatin remodeling, which ultimately determine gene expression and thereby have important roles in plasma cell differentiation ( 7 ). However, the mechanisms by which epigenetic factors regulate plasma cell differentiation are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, B cells relocate to the follicle center to undergo expansion and affinity maturation to produce high-affinity long-lived PC and memory B cells. The magnitude and duration of the EF and GC responses rely on signals from the microenvironment [8], epigenetic and transcriptional cues [9] as well as on metabolic reprogramming [10]. In the CLP model, impaired GC formation results in a reduced antigen-specific antibody response [2,3,11].…”
Section: Introductionmentioning
confidence: 99%